Exploring Pre-Service EFL Teachers’ Beliefs About Learning English in the Tertiary Ecuadorian Context - Litardo Cortez, Jenny Maylyn; Coutinho dos Santos, Jardel (Arandu UTIC, 2025)
This study describes the beliefs of pre-service EFL teachers in the tertiary Ecuadorian context, to identify their perceptions of English language learning and analyze whether these beliefs vary according to their semester of training. Using a Spanish-adapted version of the Beliefs About Language Learning Inventory (BALLI) questionnaire, the researchers administered surveys to 317 students from different academic levels, and they employed a multivariate analysis of variance (MANOVA) to examine the differences between groups. The results reveal that pre-service EFL teachers hold both beneficial and limiting beliefs, which are not static but change throughout their academic training. Furthermore, the study highlights the importance of implementing pedagogical interventions aimed at modifying misconceptions and promoting positive attitudes towards English learning to improve the quality of teaching in the Ecuadorian context. This study contributes to the understanding of future teachers’ conceptions in Ecuador, providing a basis for developing more effective and contextualized training programs.